Establishing reference ranges for thyroid function and thyroid antibody tests among Malaysian adults - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Korean Thyroid Association, 2017)
The aim of this study is to provide normal reference ranges for serum thyroid stimulating hormone (TSH), free thyroxine (fT4) and triiodothyronine (fT3), antithyroperoxidase (anti-TPO) and antithyroglobulin (anti-TG) antibodies in Malaysia. A cross sectional study involving 2190 subjects selected from 5 assigned regions which were representative of the socioeconomic and geographical background in Malaysia was performed. The median concentrations of TSH, fT4 and fT3, antiTPO and antiTG antibodies were determined from 2054 subjects who did not report any history of thyroid diseases nor taking any thyroid medications (disease-free population). A reference sub-population of 658 subjects was selected from the disease-free population by excluding those who had detectable thyroid antibodies, or biochemical hypo- or hyperthyroidism. The influence of demographic factors on serum TSH, fT4, fT3 and thyroid antibodies was also analysed. The hormonal assays and thyroid antibodies were performed using chemiluminescent microparticle immunoassays by the Architect and Immulite systems respectively. The median concentrations of thyroid hormones and antibodies among the disease free population were TSH 1.16(0.83,1.61)uIU/mL; fT4 12.98(11.99,13.97)pmol/L; fT3 4.10(3.71,4.48)pmol/L; antiTPO 12.8(<10.0,20.4)IU/mL and antiTG <20.0(<20.0,250.7)IU/mL [expressed as median(5th, 95th centiles)]. For the reference population, the median TSH was 1.14(0.83,1.55)uIU/mL with 0.32 and 3.55uIU/mL being the lower and upper limit of normal respectively. TSH levels did not differ between genders while the Indian ethnic group had higher TSH and fT4 levels with greater number of subjects possessing high antiTPO and antiTG levels albeit both total and disease free populations. As age increases, TSH and antiTPO levels increased, fT3 reduced while fT4 remained unchanged. The reference range for TSH level in the adult population of Malaysia was 0.32 – 3.55uIU/mL. The TSH and antiTPO levels increased and fT3 levels decreased with age across all the ethnic groups indicative of inherent physiological changes that occurred with aging.